(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The objective of the study is to describe the satisfaction of inpatients of the traditional medicine department with medical examination and treatment activities at Thanh Ba District Health Center, Phu Tho province in 2024 and some influencing factors. Methods: A cross-sectional descriptive study was conducted on 261 patients using the assessment tool based on Decision No. 3869/QĐ-BYT of the Ministry of Health. Satisfaction levels were measured using a Likert scale: <4 points as dissatisfied and ≥4 points as satisfied. The association was analyzed using odds ratio (OR) and 95% confidence interval (CI). Results: The results showed that the rate of inpatients receiving traditional medicine treatment at Thanh Ba District Health Center, Phu Tho Province, was generally satisfied with the medical services (91.6%) and the average overall satisfaction score was high (4.2 points/5 total points). Patients with a high level of education from junior high school or higher, unmarried/widowed/divorced/separated patients, and patients living further from the hospital had a higher rate of satisfaction with traditional medicine examination and treatment services. Conclusion: The percentage of patients receiving traditional inpatient treatment at Thanh Ba District Health Center, Phu Tho province who are generally satisfied with medical services is very high. It’s necessary to implement a larger and qualitative research to provide evidence of satisfaction of patients treated with traditional medicine in the province.